2014
DOI: 10.2105/ajph.2014.302035
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Process Improvement Intervention on Delivery of HIV Services to Offenders: A Multisite Trial

Abstract: Objectives. We tested a modified Network for the Improvement of Addiction Treatment (NIATx) process improvement model to implement improved HIV services (prevention, testing, and linkage to treatment) for offenders under correctional supervision. Methods. As part of the Criminal Justice Drug Abuse Treatment Studies, Phase 2, the HIV Services and Treatment Implementation in Corrections study conducted 14 cluster-randomized trials in 2011 to 2013 at 9 US sites, where one correctional facility received training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…17,18 Local change teams doubled the odds of successful delivery of HIV services (point estimate for odds ratio ¼ 2.14) and increased health care staff perceptions of the value of HIV services compared to the control group. 19,20 From a public health viewpoint, the disproportionate burden of HIV in incarcerated populations presents both a challenge and an opportunity. Correctional facilities provide an opportunity to engage a traditionally ''hard to reach'' demographic that often slips through the conventional community-based health system.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Local change teams doubled the odds of successful delivery of HIV services (point estimate for odds ratio ¼ 2.14) and increased health care staff perceptions of the value of HIV services compared to the control group. 19,20 From a public health viewpoint, the disproportionate burden of HIV in incarcerated populations presents both a challenge and an opportunity. Correctional facilities provide an opportunity to engage a traditionally ''hard to reach'' demographic that often slips through the conventional community-based health system.…”
Section: Discussionmentioning
confidence: 99%
“…36,60 Evaluation of client outcomes (i.e., increases in HIV testing and linkage to community treatment upon release) were negligible. 35 However, inmates in experimental correctional facilities did demonstrate an increase in awareness of HIV and perceived relevance of HIV services. 41 …”
Section: Implementation Of Hiv Testing and Linkage To Hiv Community Cmentioning
confidence: 94%
“…Pearson et al 35 found that out of two cluster-randomized trials focused on increasing opt-out HIV testing, there was no significant overall effect of increased HIV testing between experiment and control conditions (logOR=0.16, 95%CI: −0.24–0.57). Trial-specific analyses revealed a significant effect for one trial (logOR=0.37SE=0.07) and closer examination of both intervention sites reported increases in uptake of testing of up to 23%.…”
Section: Effectiveness Of Hiv Testing and Linkage To Hiv Community Camentioning
confidence: 99%
See 1 more Smart Citation
“…Baltimore City also has high rates of heroin, cocaine and substance abuse; by one estimate 1 in 8 adults needs substance use treatment (6). Baltimore also has an incarceration rate that is three times the national average and PLHIV with an incarceration history experience gaps in ART and health care access both within prisons and when they reintegrate into communities (7–10). It is within this context of high levels of poverty, incarceration and substance use disorders that PLHIV in Baltimore and their informal caregivers are living with and managing HIV and other often highly stigmatized chronic conditions.…”
Section: Introductionmentioning
confidence: 99%